Constraints on the Timing and Extent of Deglacial Grounding Line Retreat in West Antarctica - Venturelli, Ryan A.; Boehman, Brenna; Davis, Christina; Hawkings, Jon R.; Johnston, Sarah E.; Gustafson, Chloe D.; Michaud, Alexander B.; Mosbeux, Cyrille; Siegfried, Matthew R.; Vick‐Majors, Trista J.; Galy, Valier; Spencer, Robert G. M.; et al. (AGU advances, 2023)
Projections of Antarctica's contribution to future sea level rise are associated with significant uncertainty, in part because the observational record is too short to capture long‐term processes necessary to estimate ice mass changes over societally relevant timescales. Records of grounding line retreat from the geologic past offer an opportunity to extend our observations of these processes beyond the modern record and to gain a more comprehensive understanding of ice‐sheet change. Here, we present constraints on the timing and inland extent of deglacial grounding line retreat in the southern Ross Sea, Antarctica, obtained via direct sampling of a subglacial lake located 150 km inland from the modern grounding line and beneath >1 km of ice. Isotopic measurements of water and sediment from the lake enabled us to evaluate how the subglacial microbial community accessed radiocarbon‐bearing organic carbon for energy, as well as where it transferred carbon metabolically. Using radiocarbon as a natural tracer, we found that sedimentary organic carbon was microbially translocated to dissolved carbon pools in the subglacial hydrologic system during the 4.5‐year period of water accumulation prior to our sampling. This finding indicates that the grounding line along the Siple Coast of West Antarctica retreated more than 250 km inland during the mid‐Holocene (6.3 ± 1.0 ka), prior to re‐advancing to its modern position. Plain Language Summary Our continuous observations of the Antarctic Ice Sheet cover only the last three decades, so we must employ the geologic record to contextualize our ongoing observations and improve models that predict Antarctica's future contributions to sea level rise. In this study, we melted through over 1 km of ice to collect sediment and water from a freshwater lake at the base of the West Antarctic Ice Sheet. We found that this region, now 150 km from the modern ocean, was part of the marine environment only a few thousand years ago. That past connection to the ocean is powering today's population of microbial life, which moves carbon from the sediment to the water column in the lake and is eventually flushed into the Southern Ocean. We calculated the rates of carbon transfer and found that ice retreat following the Last Glacial Maximum did not stop at our study site but must have extended much farther inland. Our work highlights that we have not yet sampled the maximum extent of the last deglaciation. Investigating the conditions that enabled Antarctic ice to re‐advance from this far inland position may help inform us about how the ice sheet may be able to recover from the ongoing ice mass loss. Key Points We used clean‐access hot water drilling to sample water and sediment from an active subglacial lake in West Antarctica The presence of natural‐level radiocarbon in sediment and water samples enabled us to trace the subglacial carbon cycle We find that the deglacial extent of grounding line retreat reached up to 250 km inland of present before re‐advancing in the Holocene